USAHA KECIL LIDAH BUAYA DI KABUPATEN BOGOR: SEBUAH ANALISIS SOSIAL, EKONOMI DAN LINGKUNGAN - Hermanto Siregar; Widyastutik Widyastutik; Heti Mulyati (Jurnal Manajemen & Agribisnis, 2008)
Aloe vera’s industry is an important plant for the development of social, economy and environment. Bogor sub province is one of the area target for improving aloe vera small enterprise in Indonesia. The objective of his study is to analyze the impact of aloe vera enterprises on the social, economy and environment. The results showed that 14 desa in 9 kecamatan has potency to development of aloe vera’s enterprises. There are Kecamatan Kemang, Rancabungur, Bojong Gede, Pamijahan, Cibungbulang, Parung, Darmaga, Cijeruk dan Caringin. The sex of 91,30persen respondent is male, the background of education is dominated by Senior high school (38,89persen). The area of planting is 0.25 - 5 Ha. Theeffect of social is labor absorbent to reduce unemployment. The worker of Aloe vera was domitaned by the worker from outer family. The other effect improves earning distribution, saving and consumption community. The downstream industry of aloe vera were harvest and post harvest tools/machines andfertilizers. The upstream industry were aloe drinks, aloe foods, the raw materials for cosmetics and pharmacies. 85persen of Aloe planting produced solid wastes but it can be degradable and used for fertilizers.